Statistical analysis of store release from a weapon bay at transonic mach number - Bacci, David; Saddington, Alistair J. (Elsevier, 2026)
Numerical analysis was conducted on the release of an air-to-air missile model from a rectangular cavity geometry, having a length-to-depth ratio of 4.5 and a width-to-depth ratio of 1. Computational Fluid Dynamics was coupled with a 6-degrees-of-freedom solver using the Stress-Blending-Eddy-Simulation turbulence model to calculate the store trajectory. The release procedure was performed at a freestream Mach number of 0.9. The study aimed to correlate cavity aero-acoustic data with missile flight, comparing flow resonant modes with store trajectory evolution. The store was released at 30 different intervals during the evolution of the flow within the cavity, to encompass the effects on trajectory dispersion due to the intrinsic unsteady nature of the flow field. Correlation analysis, based on the Hilbert-Huang transform, evidenced a direct effect of flow-field resonant modes on the weapon’s roll rate and final roll angle.
Keywords: 4012 Fluid Mechanics and Thermal Engineering; 4001 Aerospace Engineering; 40 Engineering; 46 Information and computing sciences; Weapons bay; Cavity flow; Store release